2019
DOI: 10.17711/sm.0185-3325.2019.017
|View full text |Cite
|
Sign up to set email alerts
|

Presence of depressive symptoms in medical students in a Mexican public university

Abstract: Introduction. During their professional training, medical students are subject to diverse stress-causing factors such as academic demands and a highly competitive environment which may threaten their mental health. Objective. Identify the presence of depressive symptoms in medical students in a public university in Mexico. Method. Descriptive cross-sectional study of a random sample of 203 medical students at the Universidad Autónoma de Baja California from February to April 2018. The PHQ - 9 scale was used, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The depression rate was higher in women than in men in both surveys, in women, it went from 20.67% in April to 42.6% in December; in the case of men, it went from 11.54% in April to 34.62%. These results confirm the higher prevalence of depression in women, which has been observed in the general population ( Lim et al., 2018 ), in college students ( Auerbach et al., 2018 ), and particularly in medical students ( Pacheco et al., 2019 ; Tadeo-Álvarez et al., 2019 ), which manifests itself in pre-pandemic studies and is confirmed during the pandemic by COVID-19 ( Wathelet et al., 2020 ).…”
Section: Discussionsupporting
confidence: 83%
“…The depression rate was higher in women than in men in both surveys, in women, it went from 20.67% in April to 42.6% in December; in the case of men, it went from 11.54% in April to 34.62%. These results confirm the higher prevalence of depression in women, which has been observed in the general population ( Lim et al., 2018 ), in college students ( Auerbach et al., 2018 ), and particularly in medical students ( Pacheco et al., 2019 ; Tadeo-Álvarez et al., 2019 ), which manifests itself in pre-pandemic studies and is confirmed during the pandemic by COVID-19 ( Wathelet et al., 2020 ).…”
Section: Discussionsupporting
confidence: 83%
“…Our finding that depression was more likely to affect young women is consistent with other reports [ 9 , 13 15 ]. The association between gender and depression is compatible with young women being more likely to report insomnia, recurrent pain, sadness, nervousness, anxiety, anguish and depression [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…Depression and anxiety were measured using a validated Spanish version of the nine-item Patient Health Questionnaire depression scale (PHQ-9) and seven-item Generalized Anxiety Disorder scale (GAD-7). 13 15 To measure QoL, we used a validated version of the MOS/RAND 36-item Short Form Health Survey (SF-36) in Spanish for the Mexican population. 16 The characteristics of SF-36 measurement have been extensively studied to assess its reliability and validity.…”
Section: Methodsmentioning
confidence: 99%